2021
DOI: 10.1186/s13020-021-00472-9
|View full text |Cite
|
Sign up to set email alerts
|

The toxicology and detoxification of Aconitum: traditional and modern views

Abstract: Aconitum carmichaeli Debx.-derived herbal medicine has been used for anti-inflammation and anti-arrhythmia purpose for more than two thousand years. It is processed into Chuanwu (Radix Aconiti praeparata) and Fuzi (Radix Aconiti lateralis praeparata) in Traditional Chinese Medicine, which are two useful drugs but with toxic properties. There have been patients poisoned by accidental ingestion of Aconitum plants or misuse of the herbal drug, and this is of great concern to study in-depth. In this review, we pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 92 publications
0
28
0
Order By: Relevance
“…In a clinical retrospective case series study, Aconiti radix-containing herbal formulas were shown to be beneficial for human patients with CIPN symptoms [ 131 ]. Although the effects were proven in the clinical and preclinical settings as shown above, Aconitum should be carefully administered to patients because it is toxic and can be lethal if not processed properly [ 132 , 133 ].…”
Section: Candidates For New Therapeutics: Approach With Knowledge Fro...mentioning
confidence: 99%
“…In a clinical retrospective case series study, Aconiti radix-containing herbal formulas were shown to be beneficial for human patients with CIPN symptoms [ 131 ]. Although the effects were proven in the clinical and preclinical settings as shown above, Aconitum should be carefully administered to patients because it is toxic and can be lethal if not processed properly [ 132 , 133 ].…”
Section: Candidates For New Therapeutics: Approach With Knowledge Fro...mentioning
confidence: 99%
“…The facial diagnostic instrument is designed based on the theory of TCM facial diagnosis, integrating facial diagnosis image acquisition, image segmentation, and information processing. 17 , 18 The light source in the facial diagnostic instrument can affect the realism of facial color, 19 so it is crucial to keep the stability of the light source. Li et al 20 employed light-emitting diodes with color temperatures 4000 K – 11,000 K as the light source of the dark box system for facial diagnosis information collection, which enhanced the standardization of facial diagnosis information collection; Shi et al 21 concluded that D50 can be treated as an illumination light source for objectified acquisition in comparison with natural light; Zheng et al 22 used a xenon lamp with a color temperature of 5500 K to simulate a daylight light source and used a digital camera with a resolution of 4752 × 3168 to acquire images.…”
Section: Related Workmentioning
confidence: 99%
“…They are one of the most toxic plants used by humans in food and medicine (Kang et al 2012, Ali et al 2021. With the growing understanding of detoxi cation methods, the medical use of aconite is increasing (Chan et al 2021).…”
Section: )mentioning
confidence: 99%